Bioaccumulation and vertical transmission of microplastics within the poultry agri-food chain in Guayas, Ecuador - Valle-Mieles, Elsa; Pinela Castro, Douglas; Guevara Enríquez, Gabriela; Solís-Villacrés, Ricardo; González-Puetate, Iván (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
The study demonstrated that the presence of microplastics (MP) in the poultry production chain represents an emerging risk to animal health and food safety, as these particles enter primarily through feed, drinking water, and environmental dust, leading to a progressive process of bioaccumulation. Using NaCl flotation and alkaline digestion techniques, MP were quantified in feed, feces, egg yolk, yolk sac, and meconium, and statistical analyses including ANOVA, linear regression, and hierarchical clustering were applied. The results showed significant differences among matrices (p < 0.05), with the highest concentrations observed in meconium, followed by feed and feces, while egg yolk exhibited the lowest values, although these were biologically relevant due to transovarian transfer. In addition, the regression model indicated a positive relationship between production progression and MP accumulation, and the dendrogram confirmed three distinct groups: intestinal exposure, reproductive transfer, and neonatal accumulation. Taken together, these findings demonstrate that MP can cross biological barriers and be vertically transferred from the hen to the embryo, underscoring the need to implement control and monitoring strategies to reduce exposure and safeguard food safety.
Keywords: vertical transfer; food safety; polymer